Wisior opasany taśmami brązowymi z cmentarzyska kultury wielbarskiej i zagadnienie występowania bezoarów - Czyżewska, Krystyna; Dziurdzik, Bogumiła; Grabarczyk, Tadeusz; Jankun, Andrzej; Wasylikowa, Krystyna (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
A pendant encircled with bronze bands was found in 1984 during the excavations of barrow 26 in the cemetery at Odry. The grave, which has yielded the pendant, is dated to the second half of the 1st century AD. At first the object in question was thought to be a palm stone (Phoenix sylvatica). Thorough analysis, however, has shown that it is a bezoar, i.e. a globular formation produced in the stomachs of ruminants. The bezoar from Odry was composed of the hair of lynx, hare and mouse. Bezoars were worn as amulets all over medieval and modern Europe. They usually served as protection against all sorts of illnesses and complaints, notably poisoning. The find from Odry would thus represent the earliest antidote known.